A TRMM Assessment of the Composition of the Generator Current That Supplies the Global Electric Circuit. Issue 15 (6th August 2018) - Peterson, Michael; Deierling, Wiebke; Liu, Chuntao; Mach, Douglas; Kalb, Christina
Abstract: The Peterson et al. (2015, https://doi.org/10.1175/JTECH-D-14-00119.1 ) passive microwave electric field retrieval is applied to 15 years of Tropical Rainfall Measuring Mission (TRMM) satellite observations to estimate the amount of Wilson current supplied to the Global Electric Circuit from individual electrified cloud features (ECFs), which are identified as contiguous precipitating cloud regions that produce Wilson current. Current contributions from 37 million ECFs sampled by TRMM are used to examine the composition of the DC generator current. Thunderstorms are found to supply 61% of the total retrieved current, while electrified shower clouds provide the remaining 39%. ECFs over land contribute 38% of the total current, while the ocean contributions are divided between coastal oceanic regions (35%) and the open ocean (27%). The greatest share of the total TRMM‐retrieved current comes large mesoscale features (>2 × 10 3 km 2 in area) and features that have peak 20‐km electric fields in excess of 1 kVm −1 . This combination of extent and intensity leads to total currents greater than 10 A for a single ECF. The ranking of the tropical chimney regions by total current production is (1) the Americas (38%), (2) Asia (32%), and (3) Africa (15%). ECFs over the tropical Pacific Ocean contribute the remaining 15%. The Africa chimney is most prominent in total lightning activity but lags behind the others in total DC current due to a reduced frequency of electrified weather and weaker per‐storm electric fields and Wilson currents compared to the other chimneys. Plain Language Summary: Tropical Rainfall Measuring Mission satellite observations are used to estimate the amount of current each tropical electrified cloud provides to the Global Electric Circuit. Collecting these estimates more than a decade makes it possible to quantify the importance of various cloud types and the distinct "chimney" regions for the global circuit. The majority of the global generator current is supplied by thunderstorms (61%), while electrified shower clouds that do not produce lightning provide the remaining current (39%). Most of this current comes from large mesoscale storms that have electric fields at 20‐km altitude greater than 1 kVm−1 and individual current contributions exceeding 1 A. Of the three tropical chimney regions—the Americas, Africa, and Asia—Africa produced the most lightning, but the least current. This is because there are few electrified shower clouds in Africa compared to the Americas and Asia, and Africa thunderstorms appear to generate weaker electric fields and Wilson currents than their American and Asian counterparts. Key Points: Electrified cloud satellite features are used to quantify individual current contributions to the Global Electric Circuit Thunderstorms contribute 61% of the total current, while electrified shower clouds provide the remaining 39% Tropical chimney Wilson current production is ranked: (1) the Americas, (2) Asia, and (3) Africa in contrast to Africa's lightning dominance